Evaluation of competitive jammers in expert male crawl swimmers - Chollet, D.; Puel, F.; Marinho, D.; Ramos, R.; Lepretre, P.-M.; Louvet, B.; Komar, J.; Chavallard, F.; Vantorre, J.; Morio, C.; Seifert, L.; Vilas-Boas, J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The evolution of rules about competitive swimsuits requires updating current scientific data: for example, the biomechanical and physiological consequences of garments with compressive properties show mixed results (Benjanuvatra et al. 2002; Chollet et al. 2010; Marinho et al. 2012; Tomikawa & Nomura 2009). Indeed, the studies concerning swimsuits are often contradictory and some clarification is needed. Some authors showed no significant reduction in drag and no increase in buoyancy with a Fastskin swimsuit (Roberts et al. 2003; Toussaint et al. 2002) while Chatard and Wilson (2008), comparing a traditional suit, a full-body suit and a waist-to-ankle suit, found significant reduction in passive drag in the latter two. They also showed that Fastskin suits increased distance per stroke, whereas there was no significant difference in stroke rate. Mollendorf et al. (2004) tested several swimsuits and noted some small but significant differences in total drag between these suits. At low speed, pressure drag seemed to be the most important component. At high speed, skin friction drag was increased and pressure drag and wave drag were reduced for two different suits. According to Benjavunatra et al. (2002), Fastskin suits did not increase buoyancy. However, they seemed to significantly decrease active and passive drag forces when towing. In swimming, five criteria can help to define the use of appropriate swimsuits, namely 1) the discipline (e.g. triathlon, long distance, sprintt 2) the gender, 3) the morphological properties of the swimmer, 4) the physical properties of the swimmer (e.g. glide quality, buoyancyL and 5) the evolution of rules regarding these swimsuits (today limited, for men, to jammers). The logic behind using special swimsuits is to improve buoyancy what was argued in the context of triathlon (Hue, Benevante & Chollet 2003). For the same swimming speed, the improvement allowed by these suits effectively reduces the propulsive phases and increases gliding, relationship that is measured by the coordination index (ldC; Chollet, Chalies & Chatard 2000). For the distance of BOOm, this improves swimming coordination of those triathletes wearing the swimsuit (versus triathletes not wearing the swimsuit) by spending more time in non-propulsive glide during the catch phase. Besides, it was shown in a study comprising 9 females and 9 males at 100-m distance race pace (Chollet et al. 2010L that the use of Fastskin swimsuits showed no significant difference in buoyancy, glide or passive hydrostatic torque, but significantly influenced the ldC and resulted in more efficient propulsive actions for the same given speed. Indeed, the Fastskin suit significantly affected the values describing the propulsive phases: the glide phases increased and consequently propulsive phases were reduced. In accordance with previous studies, our analysis confirmed that, at increased speeds, the ldC increases (Chollet et al. 2010). The reduction in ldC with the Fastskin suits was significant for the global analysis, but a closer examination revealed that this was only significant for the 100-m velocity. lt thus appears that, besides the claims of improved buoyancy, the improvements of those new generation suits are greater for high rather than low velocities. One possible interpretation is that the compressive effect of these new suits, by reducing body volume and thus lowering buoyancy, is offset by an improvement of the drag coefficient due to this compression. The effects measured in the older generation suits, which were more useful for long distances and triathlons (Chatard et al. 1995; Hue, Benavente and Chollet 2003; Toussaint et al. 2002), no longer hold for this newest generation. The compression of body volume is thus more useful for high speeds than for slower speeds. After more than 100 world records were broken in 2008, FINA has decided to significantly modify the rules, namely that the swimmers are not allowed anymore to wear full-body, full-legs or polyurethane suits. Moreover, all accredited jammers do not have the same characteristics and their impacts on performance could be different. Hence, the aim of this study was to compare four different competitive jammers relative to the personal usual training swimsuit in well-trained swimmers, based on a large set of different tests.